High order perturbation theory for spectral densities of multi-particle excitations: S=1/2 two-leg Heisenberg ladder - Schmidt, Kai Phillip; et al. (European Physical Journal B, 2003)
We present a high order perturbation approach to quantitatively calculate spectral densities in three distinct steps starting from the model Hamiltonian and the observables of interest. The approach is based on the perturbative continuous unitary transformation introduced previously. It is conceived to work particularly well in models allowing a clear identification of the elementary excitations above the ground state. These are then viewed as quasi-particles above the vacuum. The article focuses on the technical aspects and includes a discussion of series extrapolation schemes. The strength of the method is demonstrated for S = 1/2 two-leg Heisenberg ladders, for which results are presented.